2014
DOI: 10.2196/med20.3237
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Twitter Users’ Sharing of Official New York Storm Response Messages

Abstract: BackgroundTwitter is a social network where users read, send, and share snippets of text (“tweets”). Tweets can be disseminated through multiple means; on desktop computers, laptops, and mobile devices, over ethernet, Wi-Fi or cellular networks. This redundancy positions Twitter as a useful tool for disseminating information to the public during emergencies or disasters. Previous research on dissemination of information using Twitter has mostly investigated the characteristics of tweets that are most effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Collectively, they find that URL inclusion significantly reduces retweet counts, whereas the inclusion of a hashtag significantly increases retweet counts during a wildfire (6); Burnap et al (36) observed similar results for message retransmission after a terrorist attack in the United Kingdom; and Genes et al (37) noted that the messages most retweeted during a blizzard or hurricane do not include a URL. As discussed below, our results shed light on these discrepancies.…”
Section: Message Contentmentioning
confidence: 99%
See 2 more Smart Citations
“…Collectively, they find that URL inclusion significantly reduces retweet counts, whereas the inclusion of a hashtag significantly increases retweet counts during a wildfire (6); Burnap et al (36) observed similar results for message retransmission after a terrorist attack in the United Kingdom; and Genes et al (37) noted that the messages most retweeted during a blizzard or hurricane do not include a URL. As discussed below, our results shed light on these discrepancies.…”
Section: Message Contentmentioning
confidence: 99%
“…Under quotidian conditions, the inclusion of URLs and hashtags in a message strongly influences the likelihood that the message is retweeted (4, 31); however, researchers have not found this to be true during disaster settings (6,36,37). Collectively, they find that URL inclusion significantly reduces retweet counts, whereas the inclusion of a hashtag significantly increases retweet counts during a wildfire (6); Burnap et al (36) observed similar results for message retransmission after a terrorist attack in the United Kingdom; and Genes et al (37) noted that the messages most retweeted during a blizzard or hurricane do not include a URL.…”
Section: Message Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…Twitter is one of the few widely used social media platforms that publicly document users’ immediate emotional responses to emergencies (Heverin and Zach, 2010). A number of studies have examined how the public reacted to various emergency events (Acar and Muraki, 2011; Qu et al, 2009; Vieweg et al, 2010) and how government agencies and organizations used Twitter for emergency management (Genes et al, 2014; Van Gorp et al, 2015).…”
Section: Conceptualizing Connections To Neighborhood Storytellers In mentioning
confidence: 99%
“…However, caution must be exercised in assuming that the presence of hashtags will automatically increase the number of retweets. Some researchers found that hashtags did not significantly affect sharing when they analysed tweets during a storm in New York [12]. There are a range of variables that are likely to influence retweeting and the presence of hashtags is likely to interact with some of them so that under specific conditions, the presence of hashtags may or may not have any effect on message-sharing.…”
Section: Hashtagsmentioning
confidence: 99%